Dynamics of collective organization during and across successive momentum phases in elite football matches - Gautier, H.; Cavailles, O.; Gernigon, C. (Journal of Human Sport & Exercise, 2026)
Purpose: Recent research (Gautier et al., 2024) has identified collective organization patterns associated with momentum phases in elite football. However, how these patterns evolve remains unknown. The present study aimed to identify their dynamics during momentum phases and across their succession in football matches. Method(s): Based on expert coaches' video-based descriptions of football teams experiencing positive than negative momentum (or vice versa) phases, qualitative patterns were classified according to score evolution. Results: Over the positive-then-negative momentum scenario, the frequency of patterns of "stretched block", "disconnected actions", "ball carrier far from direct opponent," and "backward defensive runs" increased, whereas the frequency of patterns of "forward block", and "compact block" decreased. Over the negative-then-positive momentum scenario, the frequency of patterns of "connected actions," "defenders close to the ball carrier", and "forward offensive and defensive runs" increased, whereas the frequency of patterns of "compact block", "forward block", "forward offensive runs", and "forward defensive runs" exhibited an increase that began even before the momentum phase transition. Conclusion(s): These findings suggest that some patterns may act as precursors or triggers of momentum transitions. Whatever the answer, these patterns can be used by coaches and players as warning signals of impending momentum transition.